Molecular evidence of Neo-tetraploids in Arabidopsis thaliana leaf elevated potassium - Nawab John, Mohamed S (2024)
Part A: Crop species that are polyploid are more likely to exhibit unique phenotypes, such as increased organ size and strong resistance to a variety of abiotic stressors that are relevant to the climate. In the model species Arabidopsis thaliana neotetraploids show elevated level in potassium (K+) in leaves. It was noted there is an alteration in well-known components of the K+ homeostasis. Mutational analysis revealed that AKT1, HAK5 and CIPK23 are not responsible for the observed increase. Instead, signalling of abscisic acid might connect with leaf elevated potassium. This review gives a brief outline about whole genome duplication and role of K+ in plants and their distribution. Also, it discusses ABA synthesis, response to neo-tetraploids.